LEGAL PERSON AS A SUBJECT OF CRIMINAL OFFENCE IN THE REPUBLIKA SRPSKA - Simović, Miodrag N. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
Although a legal person was out of the criminal law in accordance with the principle of "societas delinquere non potest" since ancient times, the tendencies in recent decades of the 20th century introduced qualitative changes into this field. Under the influence of a number of relevant international documents of universal and regional character, specific criminal legislation of the seventies of the last century accept criminal liability and punishment of legal persons, albeit of limited scope and specific character.This tendency was followed by all the criminal legislations of the states that were formed by the breakdown of the Socialist Federal Republic of Yugoslavia. There are two different tendencies: (1) the ones that separate special provisions on the liability of a legal person for criminal offences in the context of criminal legislation (Bosnia and Herzegovina, Macedonia) and (2) the ones that provide for provisions on criminal liability of legal persons in a special law – lex specialis (Slovenia, Croatia, Montenegro, Serbia). Thus, a new branch of criminal law - commercial criminal law has been constituted which turned a new page in the development of criminal law of Bosnia and Herzegovina.